Participial perception verb complements in Old English - Lowrey, Brian (Adam Mickiewicz University, 2014)
In this paper, I shall examine the complements of perception verbs in Old English involving a noun phrase and a present participle. What kind of perception is described by these structures? Do they evoke the perception of an event, or that of an entity? It will be shown here that there are good reasons to believe that an NP + present participle sequence could function as the equivalent of the traditional “AcI” construction when used with perception verbs. I shall also attempt to determine to what extent the syntax of this construction matches the semantics: is the internal argument of the perception verb the NP alone, or some kind of combination of the NP and the participle? This question is particularly interesting in the light of Declerck’s (1982) remarks on participle perception verb complements in modern English. Finally, I shall take a look at morphological parametres: sometimes the participle inflects to agree with the NP, whereas on other occasions it does not. What might the implications of this kind of variation be?
Keywords: direct perception reports; events; entities; present participles; pragmatic inference; modifiers; grammaticalisation